A Thermosetting Polyurethane with Excellent Self‐Healing Properties and Stability for Metal Surface Coating. Issue 20 (19th October 2020) - Xu, Heng; Tu, Jing; Xiang, Guifeng; Zhang, Yang; Guo, Xiaode
Abstract : Front Cover : In article number 2000273, Xiaode Guo and co‐workers report a self‐healing polyurethane material. Disulfide bonds are introduced into the hard part of the polymer chain to provide self‐healing properties for the material. The polyurethane material has excellent self‐healing perfprmance and acid‐base resistance. The stress self ‐healing can reach more than 90%, and the scratch self‐healing effect is remarkable. The self‐healing polyurethane material is applied to metal surface coating, and the coating is tested to have excellent selfhealing ability and acid‐base resistance. This work has certain significance for the research of self‐healing coating materials.